Formation scheme and some properties of a thiamine-derived pigment, pyrizepine, formed through the Maillard reaction. Issue 5 (3rd March 2022) - Kitayama, Sachiko; Igoshi, Asuka; Shimamura, Yuko; Noda, Kyoko; Murata, Masatsune
ABSTRACT: Recently, a yellow Maillard pigment named pyrizepine was identified from a heated solution containing thiamine and glucose. Here, we examined the formation scheme of this pigment and some biological properties. The mass spectrometry and nuclear magnetic resonance data of pyrizepine prepared from [6- 13 C] glucose showed that the carbon at 6-position of glucose was inserted at 2 different positions of pyrizepine. 5-(Aminomethyl)-2-methylpyridin-4-amine (AMPA), a degradation product of thiamine, was detected in the reaction solution. The pigment also formed in the solution containing AMPA in place of thiamine. These results showed that pyrizepine formed from AMPA and C4 fragments derived from glucose. Pyrizepine showed antioxidative activities in the superoxide dismutase, 2, 2-diphenyl-1-picrylhydrazyl, and H-ORAC assays. The pigment did not show mutagenicity with the Ames test. A trace amount of the pigment was detected in a pan-fried ground pork sample added glucose using liquid chromatography-tandem mass spectrometry. Graphical Abstract: